Critical Thinking and Religious Moderation in the Bahtsul Masa’il Tradition at Darus Sunnah Islamic Boarding School - Suparto Suparto; Ismi Rahmayanti; Muchammad Tholchah (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2026)
This study examines Bahtsul Masā’il at Darus Sunnah Islamic Boarding School as an institutional mechanism for internalizing religious moderation and fostering students’ critical thinking skills. Drawing on Vygotsky’s sociocultural theory, the analysis explores how dialogical interaction, collaborative reasoning, and guided participation shape students’ religious understanding within a socio‑cultural learning environment. A qualitative descriptive–analytic design was employed, using in‑depth interviews with ustaz and senior secondary (Aliyah) students, participatory observation of a Bahtsul Masā’il session, and document analysis. The findings show that Bahtsul Masā’il integrates the pesantren’s classical scholarly tradition with contextual engagement on contemporary issues, enabling students to develop tolerant, open, and reflective attitudes aligned with the values of religious moderation. The scaffolding role of musyrif, the use of digital resources, and students’ involvement in external discussion forums further enhance their analytical abilities. Challenges include uneven student preparedness and limited alignment between logic instruction and applied reasoning during discussions. While the study demonstrates the pedagogical significance of Bahtsul Masā’il, its scope is limited to a single pesantren. This study is to reveal how Bahtsul Masā’il contributes to shaping critically minded and religiously moderate students capable of addressing contemporary socio‑religious challenges in accordance with the Islamic principle of Raḥmatan lil ‘Ālamīn.